2005
DOI: 10.3168/jds.s0022-0302(05)72953-2
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression of Bovine Sodium/Glucose Cotransporter SGLT2

Abstract: The second member of the Na(+)/glucose cotransporter family, SGLT2, is a low-affinity active glucose transporter. In humans, it is predominantly located on the apical membrane of the S1 and S2 segments of renal proximal convoluted tubules, and, thus, may be mainly responsible for the reabsorption of D-glucose from the glomerular filtrate. By BLAST searching the GenBank database, we found expressed sequence tag sequences of SGLT2 in the cDNA library of bovine mammary tissues, indicating its expression in bovine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…- The members of the SGLT family also share considerable homology among the proteins (21-70% amino acid identity to SGLT1) and contain several conserved sodium:solute symporter family signatures that are characteristics of this family (GenBank accession numbers PS00456, PS00457 and PS50283). The SGLTs are predicted to have 14-15 transmembrane helices [3,16,17]. This second structural model is supported by experimental data of glycosylation studies, antibody tagging, mass spectrometry and other methods [3].…”
Section: Structural Characteristics Of Glut and Sglt Proteinsmentioning
confidence: 63%
See 1 more Smart Citation
“…- The members of the SGLT family also share considerable homology among the proteins (21-70% amino acid identity to SGLT1) and contain several conserved sodium:solute symporter family signatures that are characteristics of this family (GenBank accession numbers PS00456, PS00457 and PS50283). The SGLTs are predicted to have 14-15 transmembrane helices [3,16,17]. This second structural model is supported by experimental data of glycosylation studies, antibody tagging, mass spectrometry and other methods [3].…”
Section: Structural Characteristics Of Glut and Sglt Proteinsmentioning
confidence: 63%
“…The hydrophilic N-terminus is located on the extracellular surface of the plasma membrane. There are several consensus sites for N-linked glycosylation [16,17], however, glycosylation appears not to be required for SGLT1 activity in contrast to GLUT1 [3].…”
Section: Structural Characteristics Of Glut and Sglt Proteinsmentioning
confidence: 99%
“…lated proteins, and thus indicates the possibility of misinterpretation of immunocytochemical staining. Extrarenal expression of Sglt2 mRNA in several species has been previously proposed in kidney, liver, lung, spleen, eye, and mammary gland of several species (12,25,41,51,54,57); however, the cellular location of SGLT2 protein has not been determined. A more recent study with quantitative PCR analysis indicated a highly kidney-specific expression of Sglt2 mRNA in humans (13).…”
Section: Discussionmentioning
confidence: 99%
“…In rat, high concentrations of Sglt2 mRNA were found in the renal proximal tubule S1 segments and less in the S2 segments, whereas the S3 segments were negative (54). In bovine, low concentrations of Sglt2 mRNA were also observed in small intestine, liver, lung, spleen, mammary gland, skeletal muscle, and ciliary epithelium (12,56,57). In humans, by real-time PCR the highest concentration of Sglt2 mRNA was observed in kidneys, but a limited expression was also detected in various extrarenal organs/tissues including small intestine, liver, brain, prostate, and testis (59), whereas recent studies indicated a highly kidney-specific expression of Sglt2 mRNA (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation